A comparison between brand-specific and traditional alcohol surveillance methods to assess underage drinkers' reported alcohol use. (November 2014) - Roberts, Sarah P.; Siegel, Michael B.; DeJong, William; Jernigan, David H.
Abstract Background: Adolescent alcohol consumption remains common and is associated with many negative health outcomes. Unfortunately, common alcohol surveillance methods often underestimate consumption. Improved alcohol use measures are needed to characterize the landscape of youth drinking. Objectives: We aimed to compare a standard quantity-frequency measure of youth alcohol consumption to a novel brand-specific measure. Methods: We recruited a sample of 1031 respondents across the United States to complete an online survey. Analyses included 833 male and female underage drinkers ages 13–20. Respondents reported on how many of the past 30 days they consumed alcohol, and the number of drinks consumed on an average drinking day. Using our brand-specific measure, respondents identified which brands they consumed, how many days they consumed each brand, and how many drinks per brand they usually had. Results: Youth reported consuming significantly more alcohol (on average, 11 drinks more per month) when responding to the brand-specific versus the standard measure (p < 0.001). The two major predictors of the difference between the two measures were being a heavy episodic drinker (p < 0.001, 95% CI = 4.1–12.0) and the total number of brands consumed (p < 0.001, 95% CI = 2.0–2.8). Conclusion: This study contributes to the field of alcohol and adolescent research first by investigating a potentially more accurate alcohol surveillance method, and secondly by promoting the assessment of alcohol use among adolescents vulnerable to risky alcohol use. Finally, our survey addresses the potential impact of alcohol marketing on youth and their subsequent alcohol brand preferences and consumption.